2010
DOI: 10.1002/car.1083
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of adult survivors of severe sexual, physical and emotional institutional abuse in Ireland

Abstract: Adult survivors of institutional abuse were interviewed with a comprehensive assessment protocol which included the Childhood Trauma Questionnaire, the Institutional Child Abuse Processes and Coping Inventory, the Structured Clinical Interviews for Disorders of the Diagnostic and Statistical Manual of Mental Disorders IV axis I disorders and personality disorders, the Trauma Symptoms Inventory, a Life Problems Checklist, the Experiences in Close Relationships Inventory and the Kansas Marital Satisfaction Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 39 publications
1
10
0
3
Order By: Relevance
“…Since many trauma survivors with potentially treatable disorders seem to be reluctant to seek mental health services, we intended to investigate attitudes towards service use in a sample of adult survivors of institutional abuse with IASMHS. Institutional abuse survivors experienced sexual, physical, and/or emotional abuse in their early lives and many are affected by mental disorders and psychosocial problems in their adulthood (Fitzpatrick et al, 2010; Lueger-Schuster et al, 2013). As research on attitudes towards mental health service use in clinical samples is rather sparse, we intended to provide a first exploratory comparison of IASMHS scales in our trial with other psychological distressed samples.…”
Section: Introductionmentioning
confidence: 99%
“…Since many trauma survivors with potentially treatable disorders seem to be reluctant to seek mental health services, we intended to investigate attitudes towards service use in a sample of adult survivors of institutional abuse with IASMHS. Institutional abuse survivors experienced sexual, physical, and/or emotional abuse in their early lives and many are affected by mental disorders and psychosocial problems in their adulthood (Fitzpatrick et al, 2010; Lueger-Schuster et al, 2013). As research on attitudes towards mental health service use in clinical samples is rather sparse, we intended to provide a first exploratory comparison of IASMHS scales in our trial with other psychological distressed samples.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional rearing falls outside the range of the typical childhood environment, due to the neglect condition embedded in the structure of the institution itself negatively influencing two key domains of a child's development: cognitive and emotional (St Petersburg‐USA Orphanage Research Team, ), with potentially long‐term negative outcomes (Fitzpatrick et al ., ). The absence of a primary caregiver figure and of a stable and continuing attachment bond, even when health and nutritional needs are met, represents the main deprivation issue that faces institutionalised children (Bowlby, ).…”
mentioning
confidence: 99%
“…Mirsal et al 8 showed that the frequency of EET experienced by a sample comprising alcohol-dependent individuals (37.2% emotional abuse, 31.1% physical abuse; 11.1% sexual abuse) was significantly higher than that found in the group without such disorder (22.24% emotional abuse; 18.1% physical abuse; 3.1% sexual abuse). According to a different perspective, Fitzpatrick et al 12 and Trent et al 13 found that individuals who were victims of severe mistreatment during childhood showed very high alcoholism rates in adulthood, reaching up to 84%, depending on the type of EET they experienced.…”
Section: Introductionmentioning
confidence: 99%